How accurate approximate movements of OS sacrum movements of center of mass during roller ski skating? - Myklebust, H.; Gløersen, Ø.; Hallén, J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
An inertial measuring unit (IMU) placed on os sacrum (S1) has been used to approximate COM movements during ski skating (Myklebust et al., 2013). Floor-Westerdijk et al. (2012) found S1 to be close to COM (<10mm) during walking. However, S1 may deviate more from COM during skiing especially due to large hip flexion and upper limb movements. The purpose of this study was to quantify how accurate S1 movements estimate COM movements in V1 and V2 roller ski skating.